Effect of Link Beam Length of the Eccentric Bracing System on Seismic Rehabilitation of Weak Reinforced Concrete Frames - Niknam, Touraj; Saberi, Hamid; Saberi, Vahid; Sadeghi, Abbasali; Noroozinejad, Farsangi Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this study, a reinforced concrete (RC) reference specimen with compressive strength of 250 kg/cm2 and the weak RC specimen for seismic rehabilitation with compressive strength of 150 kg/cm2 were examined in two types of structures with 6 and 12-stories. The link beam lengths of 50, 80, and 100 cm have been used in 6 and 12-stories prototypes under the effect of 7 earthquake records. The nonlinear dynamic analyses are performed.
Keywords: reinforced concrete frame; link beam length; renovation; rama żelbetowa; belka łącząca; renowacja